Using Automated Continuous Flow Chemistry to Innovatively Synthesize β-linked 2-deoxy-sugar - Pierre-Louis, Jennifer R. (Tufts Archival Research Center, 2023)
Most of the world's antibiotics and anti-cancer chemotherapeutics are derived from natural products, due to their wide arrays of biological activity. Carbohydrates are frequently found on these natural products and can play a variety of roles in their biological activity. More specifically, altering oligosaccharides that contain β-linked 2-deoxy-sugars can modulate a natural product’s bioactivity, which can reduce undesirable side effects. However, the stereoselective synthesis of β-linked 2-deoxy-sugar disaccharides and oligosaccharides is difficult. Previous work in the Bennett lab demonstrated that activation of hemiacetal with sulfonyl chlorides resulted in species that underwent stereoselective synthesis of β-linked 2-deoxy-sugars through an α-linked glycosyl tosylate intermediate. This project will investigate the automated synthesis of β-linked 2-deoxy-sugars. The first glycosylation converted to a flow system and optimized will use 4-methoxyphenol (PMP) as a nucleophile. Converting a reaction as sensitive as a stereoselective glycosylation to flow can be difficult because many variables must be taken into consideration, as the optimized batch procedure may differ in flow. Optimization variables such as temperature, flow rate, and concentration were explored. The parameter that had a significant impact on the yield was temperature. Specifically, at a higher temperature, there is an increase in yield, which we did not anticipate based on previous batch studies. Therefore, future directions are to explore the temperature dependency of this reaction and consider variables such as flow rate, residence time, and concentrations as ways to improve the yield of the reaction.; Thesis (B.S.)--Tufts University, 2023.; Submitted to the Dept. of Chemistry.; Committee: Clay Bennett, Ira Caspari-Gnann, Luke Davis.